2011
DOI: 10.1016/j.visres.2011.07.010
|View full text |Cite
|
Sign up to set email alerts
|

The role of search difficulty in intertrial feature priming

Abstract: Previous research has shown that intertrial repetition of target and distractors task-relevant properties speeds visual search performance, an effect known as priming of pop-out (PoP). Recent accounts suggest that such priming results, at least in part, from a mechanism that speeds post-selectional, response-related processes, the marker of which is an interaction between repetition of the target and distractor features and repetition of the response from the previous trial. However, this response-based compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
41
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 38 publications
(51 citation statements)
references
References 31 publications
10
41
0
Order By: Relevance
“…Our results show that intertrial feature priming interacts with repetition of the motor response and that, although repetition of the response attribute improves search performance, it does not modulate the magnitude of intertrial priming. Finally, our results replicate the findings reported by Lamy et al (2011) by showing that the response-related component of intertrial feature priming is more likely to be observed when the search is difficult.…”
Section: Summary Of the Findingssupporting
confidence: 91%
See 2 more Smart Citations
“…Our results show that intertrial feature priming interacts with repetition of the motor response and that, although repetition of the response attribute improves search performance, it does not modulate the magnitude of intertrial priming. Finally, our results replicate the findings reported by Lamy et al (2011) by showing that the response-related component of intertrial feature priming is more likely to be observed when the search is difficult.…”
Section: Summary Of the Findingssupporting
confidence: 91%
“…This finding led us to conclude that the postselection component of feature priming reflects a heuristic strategy that observers tend to use when the search is difficult. The present finding that color repetition interacts with repetition of the motor response but not with repetition of the response attribute suggests that when the search context on the current trial (i.e., the target and distractor colors; see Lamy et al, 2011) is similar to that of the previous trial, participants are more likely to reactivate the motor response associated with the previous trial.…”
Section: Summary Of the Findingsmentioning
confidence: 54%
See 1 more Smart Citation
“…Other studies have also shown that when search becomes difficult, priming may play a less dominant role than strategy based top-down search (e.g. [71]). …”
Section: Feature-based Attention and Historymentioning
confidence: 99%
“…An important implication of this hybrid view is that recent studies showing that episodic retrieval can impact singleton search performance from one trial to the next does not preclude the presence of early perceptual-processing benefits that are due to activation/ suppression mechanisms. Although the details of when one or the other process is responsible for PoP effects require additional study, it has also been suggested that episodic influences tend to be expressed in performance when search stimuli can be perceived as integrated objects (Kristjánsson, Ingvarsdóttir, & Teitsdóttir, 2008) or when target-distractor discriminability is low, thus making search less efficient (Asgeirsson & Kristjánsson 2011;Lamy, Zivony, & Yashar, 2011;.…”
mentioning
confidence: 99%